Thermal design and on-orbit performance of the ECOSTRESS instrument. Issue 1 (March 2020) - Cha, J; Carroll, B; Rodriguez, J; Maynard, K; Romero, M
Abstract: The ECOSystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) instrument, launched on June 29, 2018, has completed nine months of operation in space. ECOSTRESS is a multi-spectral thermal infrared imaging radiometer and its primary mission is to investigate and understand how climate change affects water and carbon usage on Earth. The thermal control subsystem consists of a combination of active and passive components to maintain instrument components within the allowable flight temperature limits. Its focal plane detector is cooled to 65K by a pair of mechanical cryocoolers and a third mechanical cryocooler cools an intermediate cold shield to 130K. The heat dissipation generated by cryocoolers and electronics, is removed through non-planar cold plates and tube-on plate heat exchanger, which are cooled by a circulating fluid loop inside JAXA's JEM-EF module. The heat collected by the JEM-EF fluid is exchanged with a fluid loop that circulates through radiators located on the exterior of the Space Station. This paper provides an overview of the thermal and cryogenic system design, thermal analysis results and reviews the on-orbit thermal performance.